2021
DOI: 10.3389/fnut.2021.694775
|View full text |Cite
|
Sign up to set email alerts
|

Eat Well to Fight Obesity… and Save Water: The Water Footprint of Different Diets and Caloric Intake and Its Relationship With Adiposity

Abstract: Water scarcity and excess adiposity are two of the main problems worldwide and in Mexico, which is the most obese country in the world and suffers from water scarcity. Food production represents 90% of a person's water footprint (WF), and healthy diets can lead to less WF than do unhealthy diets related to obesity. We calculated the WF of the diet and caloric intake of adults in Mexico and analyzed its relationship with adiposity. Also, the risk of water expenditure due to adiposity and adherence to dietary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
0
10
0
2
Order By: Relevance
“…Values under those specified will be considered controls (110) . A waist circumference above 80 cm in women and 90 cm in men will be used to determine cases when these figures are equal or over, and controls when subjects have a waist circumference less than those indicated above (4,111) . Cases and controls regarding visceral fat will be determined with the manuals of the bioimpedance scale TANITA BC-601 FITSCAN® (112) , considering levels above or below 12, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Values under those specified will be considered controls (110) . A waist circumference above 80 cm in women and 90 cm in men will be used to determine cases when these figures are equal or over, and controls when subjects have a waist circumference less than those indicated above (4,111) . Cases and controls regarding visceral fat will be determined with the manuals of the bioimpedance scale TANITA BC-601 FITSCAN® (112) , considering levels above or below 12, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The process of design of the NutriSOS study is shown in Table 1. The process of understanding the behavior, including the problem definition (2)(3)(4)6,47) , the selected target behaviors, and what needs to be modified from them (13,17,32,(48)(49)(50) , are described. Also, the chosen intervention functions (51) and the selected policy categories from the behavior change wheel model are presented.…”
Section: Behavior Change Intervention Design Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthy diets are generally assumed as sustainable, and although in some cases it is true, this cannot be generalised (Lares-Michel et al, 2021). Indeed, some studies have found that shifting current dietary patterns to dietary guideline recommendations would increase dietary environmental impact in several ways; for example, an increase of 15% in blue water footprint, 34% in energy use, 7% in dietary greenhouse gas emissions, and 34% in fertiliser use (Birney et al, 2017).…”
Section: Healthy Diet’s Composition and Its Effects On The Gut Microb...mentioning
confidence: 99%